Depressive symptom factors and their differential association with psychotherapy outcomes in late-life depression: Results of the CBTlate study - Heser, Kathrin; Dafsari, Forugh Salimi; Kleineidam, Luca; KussGondorf, Katarina; Luppa, Melanie; Peters, Oliver; Frölich, Lutz; Riedel-Heller, Steffi Gerlinde; Schramm, Elisabeth; Hautzinger, Martin; Wagner, Michael; Jessen, Frank; et al. (Journal of affective disorders, 2025)
Objective - Depression is characterized by heterogeneous symptom patterns. We investigated different facets of depressive symptoms and their role in predicting the longitudinal outcome of psychotherapy in late-life depression (LLD). - Methods - This is a secondary analysis of a multicenter, randomized clinical trial in 229 LLD patients. The factor structure of the Geriatric Depression Scale (GDS) was examined. The association between these identified GDS factors and longitudinal psychotherapy outcomes (remission, response, GDS change scores) was analysed using logistic and linear regression. - Results - Five GDS factors were identified at baseline (“worries and tension”, “hopelessness and worthlessness”, “positivity and appreciation of life”, “cognitive and performance-related disturbances”, “social withdrawal”). Higher factor scores in “positivity and appreciation of life” and “social withdrawal” were associated with better psychotherapy outcomes. More specifically, “positivity and appreciation of life” predicted remission at the end of treatment (e.g., OR, 1.95 [95%CI, 1.18-3.22]; p = .009). “Social withdrawal” predicted remission at follow-up (e.g., OR, 1.86 [95%CI, 1.17-2.95]; p = .009) and response at the end of treatment (e.g., OR, 1.80 [95%CI, 1.17-2.76]; p = .008) and follow-up (e.g., OR, 1.93 [95%CI, 1.22-3.04]; p = .005). - Conclusions - Resilience factors were associated with better outcomes at the end of treatment. Social withdrawal might have been reduced by high-frequent psychotherapy sessions. Positive associations between social withdrawal and better psychotherapy outcomes remained not only at the end of treatment, but also in the long-term at follow-up. Our results might assist in treatment decision-making and improve treatment efficacy in LLD patients by developing targeted, personalized interventions.
Online veröffentlicht: 30. Juni 2025, Artikelversion: 5. Juli 2025
Gesehen am 18.08.2025